Mom's guide to child NObesity an illustrated guide book on child obesity and proper, nutritious and balanced meal preparations for mothers in Metro Manila - Vicente, Pamela Beatriz C.
There is a very one-sided view of what malnutrition is in our country. Most media present nutritional problems as underweight and undernutrition, due to this other effects of improper nutrition have been overlooked and been allowed to grow. Child overweight and obesity is something not often talked about in the Philippines, but throughout the years it has been a consistently expanding problem that can no longer be ignored.